Assessing viscoelasticity of shear wave propagation in cervical tissue by multiscale computational simulation. Issue 9 (25th June 2015) - Peralta, L.; Rus, G.; Bochud, N.; Molina, F.S.
Abstract The viscoelastic properties are recently being reported to be particularly sensitive to the gestation process, and to be intimately related to the microstructure of the cervical tissue. However, this link is not fully understood yet. In this work, we explore the importance of the heterogeneous multi-scale nature of cervical tissue for quantifying both elasticity and viscosity from shear waves velocity. To this end, shear wave propagations are simulated in a microscopic cervical tissue model using the finite difference time domain technique, over a wide frequency range from 15 to 200 kHz. Three standard rheological models (Voigt, Maxwell and Zener) are evaluated regarding their ability to reproduce the simulated dispersion curves, and their plausibility to describe cervical tissue is ranked by a stochastic model-class selection formulation. It is shown that the simplest model, i.e. that with less parameters, which best describes the simulated dispersion curves in cervical tissue is the Maxwell model. Furthermore, results show that the excitation frequency determines which rheological model can be representative for the tissue. Typically, viscoelastic parameters tend to converge for excitation frequencies over 100 kHz.